Possibilities and benefits of a new method of modifying conventional building materials with phase-change materials (PCMs) - Ryms, Michał; Klugmann-Radziemska, Ewa (Construction & building materials, 2019)
•Different modifications of conventional building materials with PCMs have been analysed.•Three methods of placing PCMs in bricks openings were proposed and tested.•Results of theoretical thermodynamic considerations were experimentally verified.•Experiment results proved the advantages of using aggregate as PCM carrier.•PCM enclosed in aggregate acts as a heat storing commercial product. The paper presents a current study devoted to the optimization of the amount of PCM present within traditional building materials, utilized in this case in hollow-brick walls. Authors focus on proposing an alternative to typical direct addition of PCM to existing building materials: introducing two- and three-component mixtures, based on a porous PCM carrier, which in this case was construction aggregate. Preliminary studies of the possibility of using the aggregate as a carrier, which – due to its porosity and good strength – is well suited for this purpose, were the subject of separate research providing promising results. Three ways of placing PCM in brick openings were proposed and tested: with Micronal DS 5040 X in form of microcapsule powder; with Rubitherm RT22 applied in liquid form, and finally as a porous aggregate impregnated with Rubitherm RT22. The conducted tests were based on measuring cooling time of brick samples prepared in accordance with above variants of PCM placement, which were previously heated by a solar radiation simulator to approx. 30 °C. Results of the experiments showed that the third variant – using aggregate as a PCM carrier, is the most advantageous. In this case, a minimal amount of PCM, which is relatively expensive compared to traditional construction materials, allows achieving cooling time very close to the maximum (100% for PCM without carrier), which effectively extends the stabilization period of room temperature. This way, less expensive solid-liquid PCMs can be utilized instead of Micronal DS 5040 X which is easy to use but relatively expensive due to microencapsulation. Additionally, utilizing Rubitherm RT22 captured in aggregate proved that even a material which is very difficult to apply in construction can be used to increase the energy efficiency of buildings. Similar effect was observed in the study of plaster board samples containing porous construction aggregate soaked in Rubitherm RT22.